1994
DOI: 10.2136/sssaj1994.03615995005800060005x
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt, Cadmium, and Lead Sorption to Hydrous Iron Oxide: Residence Time Effect

Abstract: The adsorption‐desorption of the divalent metal cations (Me2+) Co2+, Cd2+, and Pb2+ to hydrous ferric oxide (HFO) was investigated as a function of oxide aging and Me2+‐oxide residence time. The HFO was produced and stored for up to 86 wk. Periodically, Me2+ sorption was determined across the pH range of 2.5 to 12. In addition, the Me2+ ions were contacted with freshly produced HFO and stored at a pH that dictated that 80 to 100% of the Me2+ would be in the sorbed state; desorbability of the Me2+ was determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
141
0
7

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(159 citation statements)
references
References 0 publications
11
141
0
7
Order By: Relevance
“…As shown below, one hypothesis to explain CPT from ADS is that CPT represents greater binding strength because of multiple surface sites. We tested this hypothesis by increasing the complexation constants for the weak site to the values proposed by Ainsworth et al (1994) and Dyer et al (2003). However, the SCM still did not fit the CPT data.…”
Section: Surface Complexation Models (Scm)mentioning
confidence: 99%
See 1 more Smart Citation
“…As shown below, one hypothesis to explain CPT from ADS is that CPT represents greater binding strength because of multiple surface sites. We tested this hypothesis by increasing the complexation constants for the weak site to the values proposed by Ainsworth et al (1994) and Dyer et al (2003). However, the SCM still did not fit the CPT data.…”
Section: Surface Complexation Models (Scm)mentioning
confidence: 99%
“…13). Some workers found the need for different, actually stronger, binding constants to fit their own adsorption experimental data (Ainsworth et al, 1994;Dyer et al, 2003). Dyer et al (2003) also developed a triple layer model, in which they used bidentate Pb 2+ complexes.…”
Section: Surface Complexation Models (Scm)mentioning
confidence: 99%
“…É amplamente relatado na literatura que os processos de adsorção de elementos-traço não são completamente reversíveis. Explicações para esse fato incluem: difusão dos elementos para o interior das partículas ou microporos dos óxidos (Backes et al, 1995;Gray et al, 1998); precipitação (Farrah & Pickering, 1978); incorporação na estrutura cristalina dos óxidos (Ainsworth et al, 1994) e readsorção ao adsorvente (Davis & Upadhyaya, 1996).…”
Section: Resíduos Padronizadosunclassified
“…In most cases, studies consid ering the sorption/desorption of Cd and Pb have indicated Pb was much less desorbable than Cd (Pardo, 2000;Adhikari and Singh, 2003). However, Ainsworth et al (1994) found Cd desorption to be less than that of Pb at pH 3 on aged hydrous iron oxide. It was suggested this was most likely due to the incorporation of Cd but not Pb into the oxide mineral structure.…”
Section: Introductionmentioning
confidence: 99%